Design Of Hrm Sop At Aprila Training Institution - Fatma Tri Lestari; Evi Silvana Muchsinati (ConCEPt - Conference on Community Engagement Project, 2023)
Aprila Indonesia is a non-formal and informal educational institution engaged in community education courses and competency training which was founded in 2009. In a company, one of which is the Aprila Institute, it is important to have standards in company operations and it is also important to continue updating SOP (Standard Operating Procedures). Existing procedures are in line with changing circumstances so that there are no gaps between ongoing activities and existing SOPs, and the HRM SOPs used should be relevant and appropriate considering that SOPs are used daily. Therefore, this PkM (Community Service) activity aims to design HRM SOPs that are relevant to the Aprila Training Institute. In carrying out this PkM activity using the method of observation and interviews with the owners and employees of the Aprila Training Institute. The results of this activity are draft SOPs that can be used by the Aprila Institute, including draft SOPs for recruitment and selection of instructors, official travel, employee salaries, leave and employee permits, as well as employee training and development. Future research is expected to implement HRM SOP design in other companies engaged in goods or production.